Dementia Patients' Transition to Residential Aged Care: Carers' and Social Workers' Experiences. Issue 3 (3rd July 2019) - Fitzpatrick, Karen; Grace, Marty
ABSTRACT: Many people with dementia eventually require residential aged care, frequently preceded by a hospital admission. Family carers often find the process challenging and disempowering, as they are expected to move their family member to residential aged care quickly. This article reports on findings from a small Australian qualitative study focusing on the provision of information, support and resources, and discusses the findings in relation to person-centred care and critical social work. Social workers completed an online survey and participated in focus groups, and carers were interviewed. The research found that carers valued the information, support, and resources provided by social workers and other hospital staff. They needed time to adjust to the dementia diagnosis and wanted a supportive person to talk to about the written information. The social workers wanted an improved approach to the preparation and communication of information, and a more consistent approach to family meetings. IMPLICATIONS: There is a need to further develop and articulate the role of hospital social workers in supporting the transition to residential aged care for people with dementia and their family carers. What is valued by family carers is personal support; a team approach from the hospital; up-to-date, concise information; and guidance from a caseworker. Early diagnosis of dementia, more information about the progression of dementia, and advanced care planning would be of assistance.